Application of the Principles of Civil Procedure Law Through the Practice of the Court in the Resolution of Family Disputes in the Giri Mang Religious Courts - Haeratun (PT FORMOSA CENDEKIA GLOBAL, 2023)
To apply the fundamentals of civil procedural law, when managing the parties' cases, the judge carries out mobile court practices in order to provide justice for the community, especially those who are legally illiterate/lawless and who are far from urban areas. The purpose of this research is first, to explain the application of the principles and principles of civil procedural law through mobile court practice; secondly, to analyze the implementation of the practice of the Giri Win religious court circuit court if it is connected to the principles and principles of civil procedural law. Research methods include empirical/socio legal research type (socio legal approach). The results of this research are that religious courts make a new breakthrough through the practice of mobile courts in accordance with PERMA No. 1 of 2015 concerning integrated services for circuit courts of district courts and religious courts/syar'iyyah courts in the context of issuing marriage certificates, marriage books and marriage certificates, and is in accordance with the principles and principles of civil procedural law as stated in HIR and Rbg. Meanwhile, the data collection technique in this research was carried out using several stages starting with secondary data collection in the form of primary legal materials and secondary legal materials related to mobile court practice which is linked to the principles and principles of civil procedural law. These legal materials were obtained through interviews with authorized officials, especially judges who handle family cases through mobile court practice, in addition to the litigants